Implementasi Kegiatan P5 di SMKN 1 Kramatwatu - Bagus Putra; Furqonudin Furqonudin; Mahroni Mahroni; Alif Santa Famila; Dede Wirta; Selpi Amanda Fadillah; Muhammad Rizky; Ismah Nurul Sya’bani; Nur Muklis; Bagas Aji Prasetyo; Ikhsanudin Ikhsanudin (Jurnal Pelayanan Masyarakat, 2024)
This study aims to describe the implementation of P5 activities at SMK Negeri 1 Kramatwatu. The research method used is observation with a qualitative approach. With data obtained through observation of P5 activities and journals or scientific articles and documents or files related to the implementation of P5 activities in schools. While the data analysis technique used is descriptive qualitative to describe and explain the overall data that will be concluded at the end of the study. This study concluded the implementation of P5 activities in schools with drama performances aimed at educating students about bullying and preventing bullying from occurring in schools.